An Automated Vehicle Registry System in Military Workshop, Nepali Army - Kusi, Ram Prasad; Sah, Anand Kumar (Journal of Advanced College of Engineering and Management, 2025)
“An Automated Vehicle Registry System in Military Workshop, Nepali Army” is the system designed to enhance the security and efficiency of military vehicle maintenance management by automating the processes of vehicle identification and data logging. The research employs state-of-the-art image processing techniques, notably YOLOv9 and EasyOCR, to achieve these goals. YOLOv9, trained on a custom dataset prepared by collecting a set of vehicle images in a military workshop ambience, is utilized for real-time number plate localization, offering high accuracy and speed essential for dynamic environments like military operations. Complementing this, EasyOCR, an open-source Optical Character Recognition (OCR) tool, is integrated for robust character segmentation and recognition. EasyOCR’s flexibility and performance in recognizing various fonts and languages make it an ideal choice for the diverse range of military vehicle number plates. The number plate texts extracted by EasyOCR is used as query to the database stored in MONGOdB through NodeJs application. The database holds the maintenance information related to military vehicles in JSON format. All the entries that match to that query are displayed in a web application developed using html and css. The purpose of this research project is to develop an automated system that can possibly replace the current manual registry monitoring process being practiced in NA, thereby minimizing the human error, improving operational efficiency, and enabling real-time monitoring of military vehicles repair history. The system is expected to significantly improve vehicle maintenance management process and thereby enhance the operational effectiveness within the military infrastructure by automating the retrieval of maintenance history of the vehicles that appears in the military workshop.